Пуск асинхронной машины от автономного инвертора напряжения с ШИМ с синхронизацией напряжения инвертора и сети - Жемеров, Георгий Георгиевич; Колесник, Виктор Юрьевич (НТУ "ХПИ", 2008)
В статье рассматривается система пуска асинхронной машины на основе автономного инвертора напряжения с ШИМ и последующим переключением на сеть. Особенностью системы пуска является наличие интервала параллельной работы инвертора и сети. Приведены осциллограммы, характеризующие процесс пуска при разных значениях момента на валу машины.

In the article, an energization system for an asynchronous machine is examined on the basis of a voltage source inverter with PWM and subsequent switching to the mains. The feature of the energization system is presence of parallel work interval for the inverter and the mains. Diagrams characterizing the energization process at different torques on the machine shaft are given.
Energization of an asynchronous machine from a self-contained voltage source inverter with PWM under synchronization of the voltage inverter and the mains
Keywords: асинхронная машина; инвертор; синхронизация; asynchronous motor; voltage source inverter; synchronization